Environmental education in Egypt: A preliminary assessment - Faragallah, Nouran Assyed Fadl (AUC Knowledge Fountain, 2016)
Giving that Egypt is facing serious environmental issues, Egypt needs to raise the public environmental awareness. Effective environmental education is needed to provide students with what is needed for achieving sustainability. This study aims to assess environmental education in formal education in Egypt through two approaches. The first approach is by assessing students' knowledge and attitudes towards environmental concepts. The second approach is by assessing the contribution of environmental policies to implementing environmental education. The study samples were selected from three public schools located in three different cities and villages. The research used qualitative methodology as the investigation was conducted by interviews. The study findings reveal that 90% all interviewed students had a poor level of knowledge of environmental issues; in addition school curricula need to be improved in this respect. Moreover, environmental policies do not give enough attention to environmental education. The study recommends and supports that the school curricula need improvement by adding effective environmental programs or courses, and environmental policies need to be anchored by integrated regulations in order to implement effective environmental education.